Shared Decision Making in Asthma Treatment: Using Motivational Communication to Elevate Your Consultations (Actualité en allergologie et en immunologie au Canada, 2024)
The extent to which patients are adherent to their medication regimen is critical for achieving good asthma control, preventing exacerbations, and optimizing the likelihood that patients can lead full and productive lives. Knowing this, physicians might perceive that their role is to convince their patients to comply with their prescribed medicines using educational or persuasive advice-giving strategies that focus on the health benefits of treatment compliance and the negative health consequences of non-compliance. However, evidence suggests that evoking fear of negative consequences is a poor motivator for both the adoption, and long-term maintenance, of good health behaviors such as medication adherence. In an effort to make the maladaptive behavior the ‘less desirable choice’, physicians often inadvertently become associated with the fear messages they share (through classical conditioning) and the negative emotions they elicit (through operant conditioning). This may result in physicians themselves becoming aversive to their patients, leading to patients disengaging from the therapeutic relationship and becoming resistant to treatment recommendations. In fact, treatment success depends not on the imperative to convince and control patient behavior (which defines compliance), but on the willingness to collaborate with the patient to co-construct a treatment plan that they agree with and want to follow (which defines adherence). The key takeaway is to recognize that non-collaborative communication is ineffective for behavior change and may actually be counterproductive, if not harmful.